The girl in the yellow poncho : a memoir - Zook, Kristal Brent (Duke University Press, 2023)
"At five years old, Kristal Brent Zook sat on the steps of a Venice Beach, California, motel trying to make sense of her White father's abandonment, which left her feeling unworthy of a man's love and of White protection. Raised by her working-class African American mother and grandmother, Zook was taught not to count on anyone, especially men. Men leave. Men disappoint. In adulthood she became a feminist, activist, and "race woman" journalist in New York City. Despite her professional success, something was missing. Coming to terms with her identity was a constant challenge.The Girl in the Yellow Poncho is Zook's coming-of-age tale about what it means to be biracial in America. Throughout, she grapples with in-betweenness, childhood sexual assault, economic insecurity, and multiple generations of alcoholism and substance abuse on both the Black and White sides of her family. Her story is one of strong Black women-herself, her cousin, her mother, and her grandmother-and the generational cycles of oppression and survival that seemingly define their lives. Setting out on an inner journey that takes her across oceans and continents, Zook tells the story of a little girl who never gives up on love, even long after it seems to have been destroyed. In the end she triumphs, reconciling with her father and mother to create the family of her dreams through forgiveness and sheer force of will. A testament to the power of settling into one's own authentic identify, this book tells a story of a daughter's lifelong yearning, a mother's rediscovery of lost love, and the profound power of atonement and faith to heal a broken family"--